Doped ultrahigh nickel precursor with radial structure, preparation, positive electrode material and application
By adopting a radial structure doped ultra-high nickel precursor, the problem of prone to cracks in the synthesis process of doped ultra-high nickel precursors in the prior art is solved, and the excellent electrochemical performance and higher cycling stability and safety of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411826656.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
Existing doped ultra-high nickel precursors are prone to cracks during the synthesis process, which affects the cycle stability and safety of lithium-ion batteries.
The doped ultra-high nickel precursor with a radial structure is used. The doping of the doped elements is relatively uniform, without cracks and arranged radially inside. By adding additives containing hydrogen ions and ammonium ions during the mixing process, the crystal nucleation and growth rate are adjusted to avoid uneven element doping and uneven stress.
The electrochemical performance of lithium-ion batteries containing the positive electrode material prepared with doped ultra-high nickel precursor is significantly improved, and the cycle stability and safety of the batteries are improved.
Smart Images

Figure CN119637964A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field, and relates to a radial structured ultra-high nickel doped precursor, and in particular to a radial structured ultra-high nickel doped precursor and its preparation, positive electrode material and application. Background Art
[0002] As the global demand for electric vehicles and large-scale energy storage systems grows, the performance improvement of lithium-ion batteries as key energy storage devices has become particularly important. Ultra-high nickel layered oxide LiNi x Co y Mn 1-x-y O2 is considered to be a key technology to achieve long driving range and high energy storage efficiency due to its high specific capacity and energy density. However, ultra-high nickel cathode materials are prone to structural degradation and surface side reactions during the charging and discharging process, resulting in battery performance degradation. As the basis for the preparation of cathode materials, the quality and characteristics of ultra-high nickel precursors directly affect the performance of the final product. Therefore, studying the optimized synthesis process of ultra-high nickel precursors and their cathode materials is of great significance for the development of a new generation of high-performance lithium-ion batteries.
[0003] Ultra-high nickel precursors face the challenges of structural instability and easy cracking in actual synthesis and use, resulting in performance degradation. Doping modification is considered to be an effective means to improve the structural stability and electrochemical properties of the precursor by introducing different elements. For example, by bulk doping with elements such as Al, Zr, and Mg, the lattice stability of ultra-high nickel materials can be improved, cation mixing can be reduced, and thus the cycle stability and safety of the battery can be improved. However, even with bulk doping, ultra-high nickel precursors are still prone to cracking during the synthesis process, which is due to the low strength of the Ni-O bond and improper control of the stirring intensity and reaction conditions during the synthesis process. The presence of cracks will seriously affect the cycle stability and safety of the battery.
[0004] CN116111081A discloses a kind of agglomerated multi-element positive electrode material and its preparation method, application and lithium ion battery. Its structure is Li a Ni x Co y Mn z M bO2; 0.9 ≤ a ≤ 1.1, 0.5 ≤ x < 1, 0 < y < 0.5, 0 < z < 0.5, 0 ≤ b < 0.05; M is at least one of V, Ta, Cr, La, Al, Ce, Er, Ho, Y, Mg, Sr, Ba, Ra, Zr, Fe, Ca, Zn, B, W, Nb, Cd, Pb, Si, Mo, Cu, Sr and Ti; it is a secondary particle formed by agglomeration of primary particles; the primary particles are spherical or quasi-spherical; the average particle size DS of the primary particles is 0.9 - 2.4 μm; the average particle size DL of the secondary particles is 5 - 15 μm; the value range of DL / DS is 5 - 16.
[0005] CN104409700A discloses a nickel-based lithium ion battery cathode material and a preparation method thereof, including a core, a doping layer and a coating layer; the chemical formula of the core is Li a Ni x Co y M z O2; the doping layer is a core containing M'; the coating layer contains at least M' and oxygen elements; the cathode material has a core-shell structure, and is successively the core, the doping layer and the coating layer from inside to outside.
[0006] The doped ultra-high nickel precursors disclosed in the prior art all have certain defects, such as the problem of uneven doping of doping elements and the presence of cracks. Therefore, it is crucial to develop and design a new type of doped ultra-high nickel precursor with a radial structure and its preparation, cathode material and application. Summary of the Invention
[0007] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a doped ultra-high nickel precursor with a radial structure and its preparation, cathode material and application. The doped ultra-high nickel precursor provided by the present invention has relatively uniform doping of doping elements, no cracks and a radial arrangement inside, significantly improving the electrochemical performance of a lithium ion battery including a cathode material prepared from the doped ultra-high nickel precursor.
[0008] To achieve this purpose, the present invention adopts the following technical solutions:
[0009] In the first aspect, the present invention provides a doped ultra-high nickel precursor with a radial structure. The doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the crystal grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere.
[0010] The chemical general formula of the doped ultra-high nickel precursor is (Ni x Co y Mn 1-x-y ) 1-z M z (OH) 2+δ, where 0.88 ≤ x ≤ 0.98, 0 ≤ y ≤ 0.10, 0 < z ≤ 0.10; M is a doping element, and δ is dynamically adjusted according to the valence state and content of M.
[0011] In the present invention, 0.88 ≤ x ≤ 0.98. The value of x can be, for example, 0.88, 0.90, 0.92, 0.94, 0.96 or 0.98, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.
[0012] In the present invention, 0 ≤ y ≤ 0.10. The value of y can be, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.10, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.
[0013] In the present invention, 0 < z ≤ 0.10. The value of z can be, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.10, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.
[0014] In the doped ultra-high nickel precursor provided by the present invention, the doping of the doping element is relatively uniform, there are no cracks and it is radially arranged inside, significantly improving the electrochemical performance of the lithium-ion battery including the cathode material prepared from the doped ultra-high nickel precursor.
[0015] Preferably, the M includes any one and a combination of at least two of Nb, Mo, W, Zr, Ti, Al, Mg, Ca or Sr. Typical but non-limiting combinations include the combination of Nb and Mo, the combination of W and Zr, the combination of Ti and Al, the combination of Mg and Ca, the combination of Ca and Sr, or the combination of Nb, Mo and W.
[0016] Preferably, the water content of the doped ultra-high nickel precursor is not higher than 0.8 wt%, and can be, for example, 0.8 wt%, 0.78 wt%, 0.76 wt%, 0.74 wt%, 0.72 wt%, 0.7 wt%, 0.68 wt%, 0.65 wt%, 0.62 wt%, 0.6 wt%, 0.55 wt%, 0.5 wt%, 0.4 wt%, 0.3 wt%, 0.2 wt% or 0.1 wt%, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.
[0017] In a second aspect, the present invention provides a preparation method of the doped ultra-high nickel precursor described in the first aspect, and the preparation method includes:
[0018] Mixing a metal mixed salt solution containing additives and dopants with a precipitant solution, a complexing agent solution and a reaction base solution to obtain a doped ultra-high nickel precursor through a co-precipitation reaction;
[0019] The additive contains hydrogen ions and ammonium ions.
[0020] In the preparation method of the present invention, during the mixing process, since the additive in the metal mixed salt solution contains hydrogen ions and ammonium ions, the hydrogen ions ionized from the additive are used to provide a certain acidity to promote the full dissolution of the dopant, and the ionized ammonium ions consume the hydroxide ions of the precipitant during the coprecipitation reaction to adjust the crystal nucleation and growth rate, which not only avoids the uneven element doping and the stress unevenness caused by it, but also promotes the precursor to grow in a radially oriented manner to further improve the stress distribution. Under the synergistic effect of the two, a crack-free and radially arranged doped ultra-high nickel precursor is obtained, thereby significantly improving the electrochemical performance of the doped ultra-high nickel precursor. Therefore, the lithium ion battery containing the positive electrode material prepared by the doped ultra-high nickel precursor has excellent electrochemical performance. In addition, the preparation method provided by the present invention does not contain other difficult-to-handle organic or inorganic additives during the reaction process, will not introduce new impurities, the process operation is simple and controllable, and it is easy to promote and use on a large scale.
[0021] Preferably, the additive in the additive solution comprises ammonium bisulfate.
[0022] Preferably, the concentration of ammonium bisulfate in the metal mixed salt solution containing additives and dopants is 0.1-1.0 mol / L, for example, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1.0 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 0.3-0.7 mol / L.
[0023] Preferably, the dopant is a soluble salt containing the doping element M.
[0024] Preferably, the dopant is any one of sulfate, nitrate or chloride salts containing the doping element M, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sulfate and nitrate, a combination of nitrate and chloride, or a combination of sulfate, nitrate and chloride.
[0025] Preferably, the concentration of the dopant in the metal mixed salt solution containing the additive and the dopant is 0.001-0.33 mol / L, for example, it can be 0.001 mol / L, 0.002 mol / L, 0.005 mol / L, 0.008 mol / L, 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.17 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L or 0.33 mol / L, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the mixing comprises a nucleation phase and a growth phase performed sequentially;
[0027] The nucleation stage comprises: adding a metal mixed salt solution containing additives and dopants, a precipitant solution and a complexing agent solution into a reaction base liquid in parallel, performing a first coprecipitation reaction, and obtaining a first slurry containing crystal nuclei;
[0028] The growth stage includes: adding a metal mixed salt solution containing additives and dopants, a precipitant solution and a complexing agent solution in parallel to a first slurry containing crystal nuclei, performing a second coprecipitation reaction, and obtaining a doped ultra-high nickel precursor.
[0029] Preferably, in the nucleation stage, the pH of the first coprecipitation reaction is controlled to be 11.3 to 12.5, and the reaction time is 2 to 6 hours.
[0030] In the nucleation stage of the present invention, the pH of the first coprecipitation reaction is controlled to be 11.3-12.5, for example, it can be 11.3, 11.5, 11.7, 11.9, 12.1, 12.3 or 12.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In the nucleation stage of the present invention, the reaction time of the first coprecipitation reaction is controlled to be 2 to 6 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, during the growth stage, the pH of the second coprecipitation reaction is controlled to be 9.6 to 10.6, for example, 9.6, 9.7, 9.8, 9.9, 10.0, 10.1, 10.2, 10.3, 10.4, 10.5 or 10.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, in the nucleation stage and the growth stage, the concentration of the complexing agent during the first coprecipitation reaction and the second coprecipitation reaction is independently controlled to be 1 to 10 g / L, for example, it can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but it is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 2 to 6 g / L.
[0034] Preferably, in the nucleation stage and the growth stage, the temperature of the first coprecipitation reaction and the second coprecipitation reaction are independently controlled to be 40-70° C. and the rotation speed is 100-600 rpm.
[0035] In the nucleation stage and the growth stage of the present invention, the temperature of the first coprecipitation reaction and the second coprecipitation reaction is independently controlled to be 40-70°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In the nucleation stage and the growth stage described in the present invention, stirring is performed during the first coprecipitation reaction and the second coprecipitation reaction, and the stirring speeds during the first coprecipitation reaction and the second coprecipitation reaction are independently controlled to be 100 to 600 rpm, for example, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm or 600 rpm, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the D50 particle size of the doped ultra-high nickel precursor obtained in the growth stage is 5 to 18 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 8 to 12 μm.
[0038] Preferably, the mixing further includes a transition phase between the nucleation phase and the growth phase.
[0039] In the transition stage, the pH of the first slurry containing crystal nuclei is gradually reduced, the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage.
[0040] Preferably, the transition phase duration is 4 to 6 hours, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h, 5.8h or 6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the gradual reduction method is to reduce the addition rate of the precipitant solution and keep the addition rates of the complexing agent solution and the metal mixed salt solution containing additives and dopants unchanged; the addition rate of the precipitant solution before the gradual reduction is the same as the addition rate in the nucleation stage, and the addition rate of the precipitant solution after the gradual reduction is the same as the addition rate in the growth stage.
[0042] Preferably, the mass fraction of the precipitant solution is 20-40wt%, for example, it can be 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, 38wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, the mass concentration of the complexing agent solution is 10-20wt%, for example, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the complexing agent in the complexing agent solution includes any one of ammonia, ammonium carbonate, ammonium bicarbonate, oxalic acid or ethylenediaminetetraacetic acid, or a combination of at least two thereof, for example, it can be a combination of aqueous ammonia and ammonium carbonate, a combination of ammonium bicarbonate and oxalic acid, a combination of oxalic acid and ethylenediaminetetraacetic acid, or a combination of aqueous ammonia, ammonium carbonate and ammonium bicarbonate.
[0045] Preferably, the complexing agent is aqueous ammonia.
[0046] Preferably, the total concentration of metal ions in the metal mixed salt solution is 1.0 to 3.0 mol / L, for example, it can be 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L or 3.0 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the metal mixed salt solution includes nickel salt, cobalt salt and manganese salt, and the nickel salt, cobalt salt and manganese salt independently include any one of sulfate, nitrate or halide or a combination of at least two of them. Typical but non-limiting combinations include a combination of sulfate and nitrate, a combination of nitrate and halide, or a combination of sulfate, nitrate and halide.
[0048] Preferably, the metal mixed salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate.
[0049] Preferably, the reaction base liquid is a mixed solution consisting of a precipitant, a complexing agent and a solvent.
[0050] Preferably, the pH of the reaction base solution is 11.4-12.8, for example, 11.4, 11.6, 11.8, 12.0, 12.2, 12.4, 12.6 or 12.8, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0051] Preferably, the concentration of the complexing agent in the reaction base solution is 1 to 10 g / L, for example, it can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the coprecipitation reaction is carried out in a protective atmosphere.
[0053] Preferably, the protective atmosphere comprises nitrogen and / or an inert gas.
[0054] Preferably, the coprecipitation reaction further includes alkali washing, water washing and drying in sequence.
[0055] Preferably, the drying temperature is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In a third aspect, the present invention provides a positive electrode material, which is prepared from the doped ultra-high nickel precursor described in the first aspect.
[0057] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode material described in the third aspect.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The doping elements in the doped ultra-high nickel precursor provided by the present invention are relatively uniform, crack-free and radially arranged inside, which significantly improves the electrochemical performance of lithium-ion batteries containing positive electrode materials prepared using the doped ultra-high nickel precursor;
[0060] (2) In the present invention, a solution containing an additive of hydrogen ions and ammonium ions is added during the mixing process, and the hydrogen ions ionized from the additive are used to provide a certain acidity to promote the full dissolution of the dopant, and the ionized ammonium ions consume the hydroxide ions of the precipitant during the coprecipitation reaction to adjust the crystal nucleation and growth rate. This not only avoids the uneven element doping and the stress unevenness caused by it, but also promotes the precursor to grow in a radially oriented manner to further improve the stress distribution. Under the synergistic effect of the two, a crack-free and radially arranged doped ultra-high nickel precursor is obtained, thereby significantly improving the electrochemical performance of the doped ultra-high nickel precursor. Therefore, the lithium ion battery containing the positive electrode material prepared by the doped ultra-high nickel precursor has excellent electrochemical performance;
[0061] (3) The preparation method provided by the present invention does not contain other difficult-to-handle organic or inorganic additives during the reaction process, does not introduce new impurities, and the process operation is simple and controllable, and can be easily promoted and used on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a SEM image of the radial structure doped ultra-high nickel precursor provided in Example 1 of the present invention.
[0063] Figure 2 This is a SEM image of the cross-section of the radial structure doped ultra-high nickel precursor provided in Example 1 of the present invention.
[0064] Figure 3 This is a SEM image of the radially structured ultra-high nickel precursor provided in Comparative Example 1 of the present invention.
[0065] Figure 4 This is a SEM image of the cross section of the radially structured ultra-high nickel precursor provided in Comparative Example 1 of the present invention.
[0066] Figure 5 This is a SEM image of the ultra-high nickel-doped precursor provided in Comparative Example 2 of the present invention.
[0067] Figure 6 This is a SEM image of the cross-section of the ultra-high nickel-doped precursor provided in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0069] Example 1
[0070] This embodiment provides a radially structured doped ultra-high nickel precursor, wherein the doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere;
[0071] The chemical formula of the doped ultra-high nickel precursor is (Ni 0.96 Co 0.02 Mn 0.02 ) 0.995 Zr 0.005 (OH) 2.01 , the water content of the ultra-high nickel-doped precursor is 0.6wt%;
[0072] The preparation method of the doped ultra-high nickel precursor is:
[0073] (1) Nucleation stage: In a nitrogen atmosphere, a metal mixed salt solution containing ammonium hydrogen sulfate and zirconium sulfate, a sodium hydroxide solution and ammonia water are added to a reaction base liquid (pH 12, ammonia concentration 4.5 g / L) in parallel, the pH is controlled to be 12, the temperature is 55° C., the stirring speed is 300 rpm, the ammonia concentration is 4.5 g / L, and a first coprecipitation reaction is performed for 4 hours to obtain a first slurry containing crystal nuclei;
[0074] (2) Transition stage: in a nitrogen atmosphere, the pH of the first slurry containing the crystal nuclei is gradually reduced, the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage; the duration of the transition stage is 5 hours, and the gradual reduction is carried out by reducing the addition rate of the sodium hydroxide solution and keeping the addition rates of the ammonia water and the metal mixed salt solution containing ammonium hydrogen sulfate and zirconium sulfate unchanged; the addition rate of the sodium hydroxide solution before the gradual reduction is the same as the addition rate in the nucleation stage, and the addition rate of the sodium hydroxide solution after the gradual reduction is the same as the addition rate in the growth stage;
[0075] (3) Growth stage: In a nitrogen atmosphere, the obtained metal mixed salt solution containing ammonium hydrogen sulfate and zirconium sulfate is added to the first slurry containing crystal nuclei in parallel with a sodium hydroxide solution and aqueous ammonia. The pH value is controlled to be 10, the temperature is 55°C, the stirring speed is 300 rpm, and the ammonia concentration is 4.5 g / L. A second coprecipitation reaction is carried out. After solid-liquid separation, alkali washing, water washing and drying are carried out in sequence to obtain a doped ultra-high nickel precursor with a D50 particle size of 10 μm.
[0076] In the above nucleation stage, transition stage and growth stage:
[0077] The total concentration of metal ions in the metal mixed salt solution containing ammonium bisulfate and zirconium sulfate is 2 mol / L, the molar ratio of nickel ions, cobalt ions and manganese ions is 96:2:2, the concentration of ammonium bisulfate is 0.5 mol / L, the concentration of zirconium sulfate is 0.01 mol / L; the concentration of sodium hydroxide solution is 30wt%; and the concentration of ammonia water is 15wt%.
[0078] Example 2
[0079] This embodiment provides a radially structured doped ultra-high nickel precursor, wherein the doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere;
[0080] The chemical formula of the doped ultra-high nickel precursor is (Ni 0.94 Co 0.03 Mn 0.03 ) 0.98 Nb 0.001 (OH) 2.003 , the water content of the ultra-high nickel-doped precursor is 0.7wt%;
[0081] The preparation method of the doped ultra-high nickel precursor is:
[0082] (1) Nucleation stage: In an argon atmosphere, a metal mixed salt solution containing ammonium hydrogen sulfate and niobium oxalate, a sodium hydroxide solution and ammonia water were added to a reaction base liquid (pH 11.6, ammonia concentration 8 g / L) in parallel, the pH was controlled to be 11.5, the temperature was 48°C, the stirring speed was 500 rpm, the ammonia concentration was 6 g / L, and a first coprecipitation reaction was performed for 5 hours to obtain a first slurry containing crystal nuclei;
[0083] (2) Transition stage: in an argon atmosphere, the pH of the first slurry containing the crystal nuclei is gradually reduced, the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage; the duration of the transition stage is 4.5 hours, and the gradual reduction is carried out by reducing the addition rate of the sodium hydroxide solution and keeping the addition rates of the ammonia water and the metal mixed salt solution containing ammonium hydrogen sulfate and niobium oxalate unchanged; the addition rate of the sodium hydroxide solution before the gradual reduction is the same as the addition rate in the nucleation stage, and the addition rate of the sodium hydroxide solution after the gradual reduction is the same as the addition rate in the growth stage;
[0084] (3) Growth stage: In an argon atmosphere, the obtained metal mixed salt solution containing ammonium hydrogen sulfate and niobium oxalate is added to the first slurry containing crystal nuclei in parallel with a sodium hydroxide solution and aqueous ammonia. The pH value is controlled to be 10.3, the temperature is 48°C, the stirring speed is 500 rpm, and the ammonia concentration is 6 g / L. A second coprecipitation reaction is carried out. After solid-liquid separation, alkali washing, water washing and drying are carried out in sequence to obtain a doped ultra-high nickel precursor with a D50 particle size of 12 μm.
[0085] In the above nucleation stage, transition stage and growth stage:
[0086] The total concentration of metal ions in the metal mixed salt solution containing ammonium bisulfate and niobium oxalate is 1.5 mol / L, the molar ratio of nickel ions, cobalt ions and manganese ions is 94:3:3, the concentration of ammonium bisulfate is 0.7 mol / L, the concentration of niobium oxalate is 0.0015 mol / L; the concentration of sodium hydroxide solution is 35wt%; and the concentration of ammonia water is 18wt%.
[0087] Example 3
[0088] This embodiment provides a radially structured doped ultra-high nickel precursor, wherein the doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere;
[0089] The chemical formula of the doped ultra-high nickel precursor is (Ni 0.92 Co 0.04 Mn 0.04 ) 0.9 Mo 0.1 (OH) 2.4 , the water content of the ultra-high nickel-doped precursor is 0.5wt%;
[0090] The preparation method of the doped ultra-high nickel precursor is:
[0091] (1) Nucleation stage: In a nitrogen atmosphere, a metal mixed salt solution containing ammonium hydrogen sulfate and sodium molybdate, a sodium hydroxide solution and ammonia water were added to a reaction base liquid (pH 12.4, ammonia concentration 3 g / L) in parallel, the pH was controlled to be 12.3, the temperature was 62°C, the stirring speed was 200 rpm, the ammonia concentration was 2 g / L, and a first coprecipitation reaction was performed for 3 h to obtain a first slurry containing crystal nuclei;
[0092] (2) Transition stage: in a protective atmosphere, gradually reducing the pH of the first slurry containing the crystal nuclei, wherein the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage; the duration of the transition stage is 5.5 hours, and the gradual reduction is carried out by reducing the addition rate of the sodium hydroxide solution and keeping the addition rates of the ammonia water and the metal mixed salt solution containing ammonium hydrogen sulfate and sodium molybdate unchanged; the addition rate of the sodium hydroxide solution before the gradual reduction is the same as the addition rate in the nucleation stage, and the addition rate of the sodium hydroxide solution after the gradual reduction is the same as the addition rate in the growth stage;
[0093] (3) Growth stage: In a protective atmosphere, the obtained metal mixed salt solution containing ammonium hydrogen sulfate and sodium molybdate is added to the first slurry containing crystal nuclei in parallel with a sodium hydroxide solution and aqueous ammonia. The pH is controlled to be 9.8, the temperature is 62°C, the stirring speed is 200 rpm, and the ammonia concentration is 2 g / L. A second coprecipitation reaction is carried out. After solid-liquid separation, alkali washing, water washing and drying are carried out in sequence to obtain a doped ultra-high nickel precursor with a D50 particle size of 8 μm.
[0094] In the above nucleation stage, transition stage and growth stage:
[0095] The total concentration of metal ions in the metal mixed salt solution containing ammonium bisulfate and sodium molybdate is 2.5 mol / L, the molar ratio of nickel ions, cobalt ions and manganese ions is 92:4:4, the concentration of ammonium bisulfate is 0.3 mol / L, the concentration of sodium molybdate is 0.253 mol / L; the concentration of sodium hydroxide solution is 25wt%; and the concentration of ammonia water is 12wt%.
[0096] Example 4
[0097] This embodiment provides a radially structured doped ultra-high nickel precursor, wherein the doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere;
[0098] The chemical formula of the doped ultra-high nickel precursor is (Ni 0.90 Co 0.05 Mn 0.05 ) 0.95 Ti0.05 (OH) 2.1 , the water content of the ultra-high nickel-doped precursor is 0.3wt%;
[0099] The preparation method of the doped ultra-high nickel precursor is:
[0100] (1) Nucleation stage: In an argon atmosphere, a metal mixed salt solution containing ammonium hydrogen sulfate and titanium tetrachloride, a sodium hydroxide solution and ammonia water were added to a reaction base liquid (pH 11.4, ammonia concentration 1 g / L) in parallel, the pH was controlled to be 11.3, the temperature was 70°C, the stirring speed was 600 rpm, the ammonia concentration was 1 g / L, and a first coprecipitation reaction was performed for 6 hours to obtain a first slurry containing crystal nuclei;
[0101] (2) Transition stage: in an argon atmosphere, the pH of the first slurry containing the crystal nuclei is gradually reduced, the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage; the duration of the transition stage is 4 hours, and the gradual reduction is carried out by reducing the addition rate of the sodium hydroxide solution and keeping the addition rates of the ammonia water and the metal mixed salt solution containing ammonium hydrogen sulfate and titanium tetrachloride unchanged; the addition rate of the sodium hydroxide solution before the gradual reduction is the same as the addition rate in the nucleation stage, and the addition rate of the sodium hydroxide solution after the gradual reduction is the same as the addition rate in the growth stage;
[0102] (3) Growth stage: In an argon atmosphere, the obtained metal mixed salt solution containing ammonium hydrogen sulfate and titanium tetrachloride is added to the first slurry containing crystal nuclei in parallel with a sodium hydroxide solution and aqueous ammonia. The pH value is controlled to be 9.6, the temperature is 70°C, the stirring speed is 600 rpm, and the ammonia concentration is 1 g / L. A second coprecipitation reaction is carried out. After solid-liquid separation, alkali washing, water washing and drying are carried out in sequence to obtain a doped ultra-high nickel precursor with a D50 particle size of 18 μm.
[0103] In the above nucleation stage, transition stage and growth stage:
[0104] The total concentration of metal ions in the metal mixed salt solution containing ammonium bisulfate and titanium tetrachloride is 3.0 mol / L, the molar ratio of nickel ions, cobalt ions and manganese ions is 90:5:5, the concentration of ammonium bisulfate is 1.0 mol / L, the concentration of titanium tetrachloride is 0.158 mol / L; the concentration of sodium hydroxide solution is 20wt%; and the concentration of ammonia water is 10wt%.
[0105] Example 5
[0106] This embodiment provides a radially structured doped ultra-high nickel precursor, wherein the doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere;
[0107] The chemical formula of the doped ultra-high nickel precursor is (Ni 0.88 Co 0.06 Mn 0.06 ) 0.98 Mg 0.02 (OH)2, the water content of the doped ultra-high nickel precursor is 0.8wt%;
[0108] The preparation method of the doped ultra-high nickel precursor is:
[0109] (1) Nucleation stage: In a protective atmosphere, a metal mixed salt solution containing ammonium hydrogen sulfate and magnesium sulfate, a sodium hydroxide solution and ammonia water are added to a reaction base liquid (pH 12.8, ammonia concentration 10 g / L) in parallel, the pH is controlled to be 12.5, the temperature is 40° C., the stirring speed is 100 rpm, the ammonia concentration is 10 g / L, and a first coprecipitation reaction is performed for 2 h to obtain a first slurry containing crystal nuclei;
[0110] (2) Transition stage: in a protective atmosphere, gradually reducing the pH of the first slurry containing the crystal nuclei, wherein the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage; the duration of the transition stage is 6 hours, and the gradual reduction is carried out by reducing the addition rate of the sodium hydroxide solution and keeping the addition rates of the ammonia water and the metal mixed salt solution containing ammonium hydrogen sulfate and magnesium sulfate unchanged; the addition rate of the sodium hydroxide solution before the gradual reduction is the same as the addition rate in the nucleation stage, and the addition rate of the sodium hydroxide solution after the gradual reduction is the same as the addition rate in the growth stage;
[0111] (3) Growth stage: In a protective atmosphere, the obtained metal mixed salt solution containing ammonium bisulfate and magnesium sulfate is added to the first slurry containing crystal nuclei in parallel with a sodium hydroxide solution and aqueous ammonia. The pH is controlled to be 10.6, the temperature is 40°C, the stirring speed is 100 rpm, and the ammonia concentration is 10 g / L. A second coprecipitation reaction is carried out. After solid-liquid separation, alkali washing, water washing and drying are carried out in sequence to obtain a doped ultra-high nickel precursor with a D50 particle size of 5 μm.
[0112] In the above nucleation stage, transition stage and growth stage:
[0113] The total concentration of metal ions in the metal mixed salt solution containing ammonium bisulfate and magnesium sulfate is 1.0 mol / L, the molar ratio of nickel ions, cobalt ions and manganese ions is 88:6:6, the concentration of ammonium bisulfate is 0.1 mol / L, the concentration of magnesium sulfate is 0.02 mol / L; the concentration of sodium hydroxide solution is 40wt%; and the concentration of ammonia water is 20wt%.
[0114] Example 6
[0115] This embodiment provides a radial structure doped ultra-high nickel precursor, which is the same as Embodiment 1 except that the concentration of ammonium bisulfate in the metal mixed salt solution containing ammonium bisulfate and titanium tetrachloride is 0.05 mol / L.
[0116] Example 7
[0117] This embodiment provides a radial structure doped ultra-high nickel precursor, which is the same as Embodiment 1 except that the concentration of ammonium bisulfate in the metal mixed salt solution containing ammonium bisulfate and titanium tetrachloride is 1.5 mol / L.
[0118] Example 8
[0119] This embodiment provides a radial structure doped ultra-high nickel precursor, which is the same as Embodiment 1 except that ammonium bisulfate is replaced by ammonium bicarbonate of the same concentration.
[0120] Example 9
[0121] This embodiment provides a radial structure doped ultra-high nickel precursor, which is the same as Embodiment 1 except that ammonium hydrogen sulfate is replaced with diammonium hydrogen phosphate of the same concentration.
[0122] Comparative Example 1
[0123] This comparative example provides a radially structured high nickel precursor, except that the chemical formula of the doped ultra-high nickel precursor is (Ni 0.96 Co 0.2 Mn 0.2 )(OH)2, that is, omitting zirconium sulfate in the metal mixed salt solution in the preparation method of the doped ultra-high nickel precursor, and the rest are the same as those in Example 1.
[0124] Comparative Example 2
[0125] This comparative example provides a doped ultra-high nickel precursor, which is the same as Example 1 except that the internal structure of the doped ultra-high nickel precursor does not show that the grains are radially arranged from the core position of the sphere to the surface of the sphere, that is, the ammonium bisulfate in the metal mixed salt solution in the preparation method of the doped ultra-high nickel precursor is omitted.
[0126] The radial structure doped ultra-high nickel precursor provided in Example 1 and its cross section were tested using a scanning electron microscope, and the SEM image of the radial structure doped ultra-high nickel precursor provided in Example 1 was obtained as shown in FIG. Figure 1 As shown, the cross-sectional SEM image is Figure 2 shown by Figure 1 and Figure 2 It can be obtained that the ultra-high nickel-doped precursor provided in Example 1 has no cracks, fine grains and a radially arranged structure inside;
[0127] The radial structure doped ultra-high nickel precursor provided in Comparative Example 1 and its cross section were tested using a scanning electron microscope, and the SEM image of the radial structure doped ultra-high nickel precursor provided in Comparative Example 1 was obtained as shown in FIG. Figure 3 As shown, the cross-sectional SEM image is Figure 4 shown by Figure 3 and Figure 4 It can be obtained that the ultra-high nickel-doped precursor provided in Comparative Example 1 has cracks, coarse grains, and a radially arranged structure inside;
[0128] The ultra-high nickel-doped precursor and its cross section provided in Comparative Example 2 were tested using a scanning electron microscope, and the SEM image of the ultra-high nickel-doped precursor provided in Comparative Example 2 was obtained as shown in FIG. Figure 5 As shown, the cross-sectional SEM image is Figure 6 shown by Figure 5 and Figure 6 It can be seen that the ultra-high nickel-doped precursor provided in Comparative Example 2 has cracks, coarse grains, and no radially arranged structure is observed inside;
[0129] A doped ultra-high nickel precursor was prepared by the preparation method provided in the above embodiment and comparative example, and the obtained doped ultra-high nickel precursor was mixed with lithium hydroxide at a mass ratio of 1:1.04 and sintered at 780° C. for 16 hours to obtain a positive electrode material;
[0130] The obtained positive electrode material is used to prepare a lithium-ion battery: the obtained positive electrode material, conductive carbon black SP (TIMCAL) and polyvinylidene fluoride PVDF (HSV900) are mixed in a mass ratio of 90:5:5, N-methylpyrrolidone is used as a solvent, and the mixture is stirred into a slurry. The obtained slurry is evenly coated on an aluminum foil with a scraper with a coating gap of 100 um; after coating, it is first blown dry, then rolled and cut into circular electrode sheets, and then vacuum dried at 120° C. and the weight of the electrode sheets is weighed to obtain a button half-cell positive electrode sheet; a metal lithium sheet is used as a negative electrode, a PP microporous membrane is used as a separator, and a lithium battery basic electrolyte is used as an electrolyte. The positive electrode sheet, the metal lithium sheet, the separator and the electrolyte are assembled to obtain a button battery;
[0131] The battery test was performed using a battery test system (Blue Electric CT2001A, Wuhan, China). The battery was first activated three times at 0.1C rate / 2.7-4.3V, and then the activated button battery was electrochemically tested at 2.7-4.3V@0.1C / 1C. The test showed that the 0.1C first discharge specific capacity of the lithium-ion battery prepared by the doped ultra-high nickel precursor provided in Example 1 was 229.8 mAh / g, and the 0.1C first discharge specific capacity of the lithium-ion battery prepared by the doped ultra-high nickel precursor provided in Example 2 was 228.5 mAh / g, the 0.1C first discharge specific capacity of the lithium ion battery prepared by the doped ultra-high nickel precursor provided in Example 3 is 225.0mAh / g, the 0.1C first discharge specific capacity of the lithium ion battery prepared by the doped ultra-high nickel precursor provided in Example 4 is 224.3mAh / g, and the 0.1C first discharge specific capacity of the lithium ion battery prepared by the doped ultra-high nickel precursor provided in Example 5 is 222.7mAh / g. The results of the 1C / 0.1C discharge capacity ratio and the 1C cycle 100-week capacity retention rate are tested and are shown in Table 1.
[0132] Table 1
[0133]
[0134] From Table 1, we can get:
[0135] (1) The lithium-ion battery prepared by the ultra-high nickel doped precursor prepared by the preparation method provided in Examples 1 to 5 has a high initial discharge capacity, excellent rate performance and strong cycle stability;
[0136] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the concentration of ammonium bisulfate in the metal mixed salt solution containing additives and dopants of the present invention affects the performance of the lithium ion battery; when the concentration of ammonium bisulfate is 0.1-1.0 mol / L, the lithium ion battery exhibits a higher initial discharge capacity, better rate performance and stronger cycle stability. This is because the hydrogen ions and ammonium ions ionized from ammonium bisulfate in the concentration range of 0.1-1.0 mol / L can react with the hydroxide ions of the solution to properly regulate the ammonia concentration and pH value, thereby regulating the growth rate of the precursor to maintain its slow radial structure growth along the radial direction. Too high or too low a concentration will affect the growth rate and affect the formation of the radial structure.
[0137] (3) By comparing Example 1 with Examples 8 and 9, it can be seen that the type of additive in the metal mixed salt solution containing additives and dopants in the present invention will affect the performance of the lithium ion battery; when the additive is ammonium hydrogen sulfate, compared with ammonium bicarbonate and diammonium hydrogen phosphate that can also provide hydrogen ions and ammonium ions, a better doped ultra-high nickel precursor can be obtained, so that the lithium ion battery has a better initial discharge capacity, better rate performance and stronger cycle stability. This is because when using ammonium bicarbonate, carbonate ions can also participate in precipitation, thereby forming uneven carbonate precipitation in a local range, which affects the quality of the precursor; while diammonium hydrogen phosphate is a weaker electrolyte, and its hydrogen ions and ammonium ions dissociate more slowly than ammonium hydrogen sulfate, and the growth process of the precursor particles cannot be timely and effectively regulated, which is not conducive to forming a better radial structure;
[0138] (4) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the combined use of the dopant and the additive in the present invention is conducive to obtaining a doped ultra-high nickel precursor with better performance, so that the lithium ion battery has a better initial discharge capacity, better rate performance and stronger cycle stability. This is because in the present invention, a solution containing hydrogen ions and ammonium ions is added to the additive during the mixing process, and the hydrogen ions ionized by the additive are used to provide a certain acidity to promote the full dissolution of the dopant, and the ionized ammonium ions consume the hydroxide ions of the precipitant during the coprecipitation reaction to adjust the crystal nucleation and growth rate, which not only avoids the uneven element doping and the stress unevenness caused by it, but also promotes the precursor to grow in a radially oriented manner and further improves the stress distribution. Under the synergistic effect of the two, a doped ultra-high nickel precursor without cracks and radially arranged inside is obtained, thereby significantly improving the electrochemical performance of the doped ultra-high nickel precursor. Therefore, the lithium ion battery containing the positive electrode material prepared by the doped ultra-high nickel precursor has excellent electrochemical performance.
[0139] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A radial structure doped ultra-high nickel precursor, characterized in that: The doped ultra-high nickel precursor is spherical, and the internal structure of the doped ultra-high nickel precursor is that the grains are radially arranged and distributed from the core position of the sphere to the surface of the sphere; The chemical general formula of the doped ultra-high nickel precursor is (Ni x Co y Mn 1-x-y ) 1-z M z (OH) 2+δ , where 0.88 ≤ x ≤ 0.98, 0 ≤ y ≤ 0.10, 0 < z ≤ 0.10; M is a doping element, and δ is dynamically adjusted according to the valence state and content of M.
2. The doped ultra-high nickel precursor according to claim 1, characterized in that: The M includes any one of Nb, Mo, W, Zr, Ti, Al, Mg, Ca or Sr, and a combination of at least two thereof; Preferably, the water content of the ultra-high nickel-doped precursor is not higher than 0.8 wt %.
3. A method for preparing the doped ultra-high nickel precursor according to claim 1 or 2, characterized in that: The preparation method comprises: Mixing a metal mixed salt solution containing additives and dopants with a precipitant solution, a complexing agent solution and a reaction base solution to obtain a doped ultra-high nickel precursor through a co-precipitation reaction; The additive contains hydrogen ions and ammonium ions.
4. The preparation method according to claim 3, characterized in that: The additive includes ammonium bisulfate; Preferably, the concentration of ammonium bisulfate in the metal mixed salt solution containing additives and dopants is 0.1 to 1.0 mol / L, preferably 0.3 to 0.7 mol / L.
5. The preparation method according to claim 3 or 4, characterized in that: The dopant is a soluble salt containing a doping element M; Preferably, the concentration of the dopant in the metal mixed salt solution containing the additive and the dopant is 0.001-0.33 mol / L.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The mixing includes a nucleation stage and a growth stage performed sequentially; The nucleation stage comprises: adding a metal mixed salt solution containing additives and dopants, a precipitant solution and a complexing agent solution into a reaction base liquid in parallel, performing a first coprecipitation reaction, and obtaining a first slurry containing crystal nuclei; The growth stage includes: adding a metal mixed salt solution containing additives and dopants, a precipitant solution and a complexing agent solution in parallel to a first slurry containing crystal nuclei, performing a second coprecipitation reaction, and obtaining a doped ultra-high nickel precursor.
7. The preparation method according to claim 6, characterized in that: In the nucleation stage, the pH of the first coprecipitation reaction is controlled to be 11.3-12.5, and the reaction time is 2-6 hours; Preferably, during the growth stage, the pH during the second coprecipitation reaction is controlled to be 9.6 to 10.6; Preferably, in the nucleation stage and the growth stage, the concentration of the complexing agent during the first coprecipitation reaction and the second coprecipitation reaction is independently controlled to be 1 to 10 g / L, preferably 2 to 6 g / L; Preferably, in the nucleation stage and the growth stage, the temperature of the first coprecipitation reaction and the second coprecipitation reaction are independently controlled to be 40-70° C., and the stirring speed is 100-600 rpm; Preferably, the D50 particle size of the doped ultra-high nickel precursor obtained in the growth stage is 5 to 18 μm, preferably 8 to 12 μm.
8. The preparation method according to claim 6 or 7, characterized in that: The mixing also includes a transition phase between the nucleation phase and the growth phase; In the transition stage, the pH of the first slurry containing the crystal nuclei is gradually reduced, the pH of the first slurry before the gradual reduction is the same as the pH in the nucleation stage, and the pH of the first slurry after the gradual reduction is the same as the pH in the growth stage; Preferably, the transition period is 4 to 6 hours; Preferably, the stepwise reduction is carried out by reducing the addition rate of the precipitant solution and keeping the addition rates of the complexing agent solution and the metal mixed salt solution containing the additive and the dopant unchanged; The addition rate of the precipitant solution before the step-wise reduction is the same as the addition rate in the nucleation stage, and the addition rate of the precipitant solution after the step-wise reduction is the same as the addition rate in the growth stage.
9. A positive electrode material, characterized in that: The positive electrode material is prepared from the doped ultra-high nickel precursor according to claim 1 or 2.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to claim 9.
Citation Information
Patent Citations
Anode material for nickel-base lithium ion battery and preparation method of anode material
CN104409700A
Cited By
High-nickel single-crystal nickel-cobalt-manganese material, preparation method thereof, positive plate and lithium ion battery
CN121472964A